Temps et musique dans la pensée d’Augustin - Charru, Philippe (Revue d'études augustiniennes et patristiques, 2009)
Augustine’s idea of music, which was worked out in the De musica around the notion of movement, cannot be separated from his reflection on time. Beginning from the defi nition of music as ‘science of movement’, Augustine is led to introduce the concept of number, a key notion in music, which is philosophically discussed by him, and which illuminates the question of the production of time. The perception of this production of time implies a kind of listening that brings with it the memory, considered here in the two dimensions of its exercice, horizontal and vertical. At the crossroads of these two dimensions, Augustine finds the basis of an experience of time opened to eternity. Music means to him the preferential way to such an experience; therefore his reflections about music and time illuminate themselves mutually.